PELATIHAN JURNAL TERAKREDITAS NASIONAL DAN INTERNASIONAL BEREPUTASI DI FAKULTAS TEKNIK INDUSTRI UNTAG SURABAYA GUNA MENUMBUHKAN KESADARAN MAHASISWA AKAN PENTINGNYA PENULISAN ARTIKEL ILMIAH - Raissa, Amanda; Yuli Satyarini Sukendar, Astri; Michael, Tomy (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Journal writing has become an important part that must be understood and also studied by students in tertiary institutions. The definition of the journal itself is a special article that contains articles in a particular field of science where in the journal writing it contains at least three people from a related institution related to a particular scientific discipline, research and also community service which will later become a reference for others who need renewable scientific resources. The refore it is very important for someone to learn and also improve their skills in writing scientific articles in the form of journals so that later someone's penchant for writing new discoveries can be useful for everyone. Therefore, in this service, accredited and internationally acclaimed journal training is held at the Untag Surabaya Industrial Engineering faculty in order to foster student awareness of the importance of writing scientific articles in the form of journals.